Neighbourliness and mutual interests in academia: The Kuala Lumpur - CLMV Dialogue An interview with the Director-General of the Department of Higher Education, MoHE, Y. Bhg. Professor Dato’ Dr. Ir. Radin Umar Radin Sohadi - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2008)

(untitled)
Malaysia has seen rapid growth in the demand for higher education. We have, over the last two decades consolidated our efforts in promoting this growth systematically and efficiently. We have a strategic plan for higher education.